2009
DOI: 10.1002/met.141
|View full text |Cite
|
Sign up to set email alerts
|

The development of a new dust uplift scheme in the Met Office Unified Model™

Abstract: Aeolian mineral dust aerosol is an important consideration in the Earth's radiation budget as well as a source of nutrients to oceanic and land biota. The modelling of aeolian mineral dust has been improving consistently despite the relatively sparse observations to constrain them. This study documents the development of a new dust emissions scheme in the Met Office Unified Model  (MetUM) based on the Dust Entrainment and Deposition (DEAD) module. Four separate case studies are used to test and constrain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 49 publications
(76 reference statements)
0
17
0
Order By: Relevance
“…This follows the implementation in a prior version of the HadGEM2 by Ackerley et al [2009Ackerley et al [ , 2012. While both schemes are based on Marticorena and Bergametti [1995] and Fécan et al [1999], the implementation of the threshold friction velocity is different.…”
Section: Alternative Dust Emission Schemementioning
confidence: 99%
“…This follows the implementation in a prior version of the HadGEM2 by Ackerley et al [2009Ackerley et al [ , 2012. While both schemes are based on Marticorena and Bergametti [1995] and Fécan et al [1999], the implementation of the threshold friction velocity is different.…”
Section: Alternative Dust Emission Schemementioning
confidence: 99%
“…where F soil is the fraction of bare soil within a grid box, C is an empirically derived constant of proportionality (defined in [25]), ρ * is the surface air density over land (kg m −3 ). M rel is the mass of dust in each bin relative to the total mass of dust at each grid point and is calculated from the silt, sand and clay fraction values taken from the International Geosphere-Biosphere Programme (IGBP) global soil data set [26], D is a globally uniform tuning parameter (set to 18 in these experiments following a series of test simulations) and TL is the "topographic low" source term (based on the work by [27]), which is calculated as:…”
Section: Dust Uplift Scheme 1: Climmentioning
confidence: 99%
“…Where H orog is half of the peak-to-trough height of the model surface elevation. The values in (3) (shown in Figure 1) were chosen following test experiments and are different to those used in [27] as a result of the lower resolution orography used in this study and the different dust uplift scheme (CLIM). The version of the horizontal flux used by [20] does not use the TL function used in this study.…”
Section: Dust Uplift Scheme 1: Climmentioning
confidence: 99%
“…A regional dust model system, LM-MUSCAT-DES, also has been developed during the 2006 Saharan Mineral Dust Experiment field campaign [Heinold et al, 2008], with a subsequent model evaluation revealing the benefits and the limitations of the model, such as inaccuracies in the location of dust sources and the description of specific meteorological features by the model. Recently, the Met Office Unified Model has been upgraded so as to include the dust emissions scheme based on the DEAD model [Ackerley et al, 2009]. The necessity for sand and dust storm prediction in East Asia has led to the development of CUACE/Dust operational forecasting system [Zhou et al, 2008]; the model evaluation revealed the significance of the utilization of detailed soil description.…”
Section: Introductionmentioning
confidence: 99%